Rancang Bangun Pembangkit Listrik Tenaga Surya untuk Kebutuhan Rumah Kebun di Kabupaten Selayar - Sapruddin, Ayu Fitriah; Nur Rahmah H. Anwar; Firman; Yiyin Klistafani; Yusuf Yunus, Muhammad; Marhatang; Shiddiq Yunus, A.M; Anastasya, Anastasya; Wulandari, Wulandari (Jurnal Teknik Mesin Sinergi, 2025)
Solar Power Plants (PLTS) are renewable-based electricity systems for areas not yet reached by the national grid. This study aims to design and test a small-scale PLTS system for lighting a farm house in Selayar Regency. The system consists of a 100 Wp solar panel, a PWM 10A charge controller, LiFePO4 batteries, and 30–40 W LED loads. The research method includes system design, assembly, and performance testing. The results show that the solar panel produced a voltage of 13.2–13.6 V, solar radiation intensity of 560–1235 W/m², and an average efficiency of 11.71%. The system meets daily energy needs of 1.260 Wh and provides lighting for 12 hours per night. This PLTS system proves effective as a clean energy solution for remote areas